Cladocalon, a new genus of net-winged beetles from Central America and Mexico (Coleoptera: Lycidae) - Nascimento, Elynton Alves Do; Bocakova, Milada (Zootaxa, 2022)
Cladocalon gen. nov. is proposed within the tribe Eurrhacini in the subfamily Lycinae including five species: C. chiriquense (Gorham, 1884) comb. nov. and C. histrionicum (Gorham, 1884) comb. nov. (transferred from Calocladon), C. bugabense sp. nov., C. mexicanus sp. nov. and C. guatemalense sp. nov. Lectotypes and paralectotypes of the two previously described species are designated. A key to species is provided and illustrations of diagnostic features are given.